Đánh giá và đề xuất biện pháp nâng cao năng lực thích ứng với công tác giảng dạy của giáo viên tiểu học tại Việt Nam trong bối cảnh đại dịch Covid-19 - Nguyễn , Thành Công; Âu , Quang Hiếu; Nguyễn , Đức Minh (Tạp chí Giáo dục, 2023)
In the context of the Covid-19 pandemic, educational institutions had to react quickly to the sudden shift from face-to-face teaching to online instructions. Accordingly, teachers were also required to update and adapt in a timely manner in organising and assessing learning, as well as promoting educational effectiveness. Based on survey data of 336 teachers, this article focuses on assessing teachers' adaptability competency in teaching in the context of Covid-19. The findings shows that the adaptability competency in teaching of primary school teachers is generally good, except for the average result in technology-related aspects. Thus, the authors propose a number of measures for education managers as well as stakeholders to support teachers in improving teaching quality in such a complicated epidemic situation.